Mitochondria-based aircraft carrier enhances in vivo imaging of carbon quantum dots and delivery of anticancer drug - Li, Wen-Qing; Wang, Zhigang; Hao, Sijie; Sun, Liping; Nisic, Merisa; Cheng, Gong; Zhu, Chuandong; Wan, Yuan; Ha, Laura; Zheng, Si-Yang (Nanoscale, 2018)
The application of engineered bacteria-based drug delivery vehicles to treat cancer has been practiced for more than a century. Mitochondria, evolutionarily originated from bacteria, are ubiquitous, semi-autonomous cellular organelles. In this study, we present the first exploration of using mitochondria as a delivery system of carbon quantum dots (CQDs) for in vivo imaging and administration of the anticancer drug doxorubicin (DOX). The results show that mitochondria as carriers are compatible with CQD loading and preserve the optical properties of CQDs. Moreover, the mitochondria delivery system can improve the CQD bio-distribution in organs and prolong the retention time of CQDs after intravenous injection. Furthermore, mitochondria loaded with doxorubicin hydrochloride (Mito-DOX) show an enhanced therapeutic effect compared to free DOX. The mitochondria-based “aircraft” system may be a promising novel therapeutic platform with high potential for biological imaging and drug delivery to fight cancer and other diseases.